2013
DOI: 10.1136/bmjopen-2013-003336
|View full text |Cite
|
Sign up to set email alerts
|

Poor glycaemic control in Brazilian patients with type 2 diabetes attending the public healthcare system: a cross-sectional study

Abstract: ObjectivesTo describe the clinical profile of Brazilian patients with type 2 diabetes attending the public healthcare system and identify factors associated with poor glycaemic control.DesignCross-sectional study.Setting14 centres in five regions of Brazil, including primary care units and outpatient clinics of University Hospitals.ParticipantsPatients with type 2 diabetes attending outpatient clinics of public healthcare system.Main outcome measuredGlycated haemoglobin (HbA1c), centrally measured by high-perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
52
2
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 10 publications
7
52
2
7
Order By: Relevance
“…Few studies were available that compared the association of SNPs with T2D in the Brazilian population. In our study, we revealed that the characteristics of the T2D group indicated poor glycemic control, as demonstrated by the concentration of the biomarkers HbA1C (> 7%) and 1,5-anhydroglucitol (< 10 µg/mL) (21,22). In addition, the minor but significant reduction in serum albumin concentration associated with high frequency of hypertension in the T2D group could suggest an increase in albumin loss (microalbuminuria) by the kidney (23,24).…”
Section: Discussionmentioning
confidence: 87%
“…Few studies were available that compared the association of SNPs with T2D in the Brazilian population. In our study, we revealed that the characteristics of the T2D group indicated poor glycemic control, as demonstrated by the concentration of the biomarkers HbA1C (> 7%) and 1,5-anhydroglucitol (< 10 µg/mL) (21,22). In addition, the minor but significant reduction in serum albumin concentration associated with high frequency of hypertension in the T2D group could suggest an increase in albumin loss (microalbuminuria) by the kidney (23,24).…”
Section: Discussionmentioning
confidence: 87%
“…Another Brazilian study performed between 2006 and 2011, with 5,750 diabetic patients seen in a public health system found mean HbA1c of 8.1% (8.6±2.2%) [6]. However, in our study, 49% of our patients were above glycemic control target, with a median HbA1c of 8.7%, a worse percentage than encountered in, for example, Germany (40%) [32], the Netherlands (42%) [33] and USA (43%) [34].…”
Section: Discussionmentioning
confidence: 99%
“…Data from several epidemiological studies worldwide have shown that the majority of patients do not obtain, nor maintain glycemic control among satisfactory range defined by international societies [4][5][6][7][8]. Thus, diabetes' management remains challenging.…”
Section: Introductionmentioning
confidence: 99%
“…O maior número de mulheres com DM tipo 2 foi verificado em outros estudos (VIANA et al, 2013;FONTBONNE et al, 2013, CAMPOLINA et al, 2013. LOYOLA FILHO et al, 2013FARIA et al, 2014).…”
Section: Discussionunclassified